2013
DOI: 10.1007/s40273-013-0074-1
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Drug Reimbursement Outcomes: A Comparative Study of the Role of Pharmacoeconomic Evidence in Dutch and Swedish Reimbursement Decision Making

Abstract: Both countries publish drug reimbursement information. Therapeutic value appears to be the most decisive criterion; the relative importance of full economic evaluations is more modest than would generally be expected, especially in The Netherlands. Although the assessment process is reasonably transparent, both countries could make the appraisal process more transparent by more explicitly showing the actual role of each different (societal) criterion in their decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 20 publications
1
30
0
1
Order By: Relevance
“…Decisions are either based on a simple cost-minimization analysis (CMA) or a cost-utility analysis (CUA) [17]. CMA (price comparison) is used when a drug is judged to be clinically equivalent to the comparator (n = 252), whereas a CUA is needed if a pharmaceutical company claims an added therapeutic value and a price premium over its comparators (n = 102).…”
Section: Datamentioning
confidence: 99%
“…Decisions are either based on a simple cost-minimization analysis (CMA) or a cost-utility analysis (CUA) [17]. CMA (price comparison) is used when a drug is judged to be clinically equivalent to the comparator (n = 252), whereas a CUA is needed if a pharmaceutical company claims an added therapeutic value and a price premium over its comparators (n = 102).…”
Section: Datamentioning
confidence: 99%
“…Based on this hierarchical model, technologies that (would subsequently) pass all criteria were to be included in the basic benefits package. The report was pivotal for the discussion on priority setting, and in the following years, the criteria were put into practice [2,6,27]. The Dutch Health Care Institute (ZiN) later reformulated these criteria as necessity of care, effectiveness, cost-effectiveness, and necessity of insurance, respectively, and supplemented these with a feasibility criterion [1,28].…”
Section: A Brief History Of Healthcare Priority Setting In the Nethermentioning
confidence: 99%
“…However, the outcomes of economic evaluations only predict such decisions to a moderate extent [3,5,6]. One explanation for this disparity is that decision makers are not exclusively concerned with maximising health given available budgets, but also with distributing health(care) equitably and fairly [3,5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…(5,6) The literature has generally examined this issue from the perspective of the last available listing recommendation, and has suggested that international differences are accounted by social determinants, including preferences for treatment, disease severity and rarity (7,8) and local clinical practice;(4) as well as methodological factors, including HTA design and sufficiency of pharmacoeconomic evidence, (7,9) and use of comparative data. (4) As has been previously argued, however, HTA is a complex process that cannot be fully understood if the perspective concentrates exclusively on final listing decisions.…”
Section: Introductionmentioning
confidence: 99%